Genetic variability and plus tree selection in natural populations of Malaveppu (Melia dubia Cav.) - Binu N.Kamalolbhavan (Department of Forest biology and tree improvement, 2019)
ABSTRACT Melia dubia commonly known as Malabar neem is a fast growing indigenous species. It is considered as a major wood in plywood and paper industries and the plant is put into various medicinal uses, preferred for use in packing cases, cigar planks etc. There are no identified genotypes of melia, suitable for Kerala. This is one of the reasons which has made a dearth in the availability of good planting material. Hence, a study was conducted to determine the genetic diversity of the trees and select plus trees from the forests of Kerala. Fifteen locations spread over eighteen localities where the species is common were identified from secondary data and reconnaissance survey. In total 281 trees were selected for the survey. The important quantitative and qualitative characters of the trees were determined. Based on baseline selection system, a regression analysis was done between the (DBH)2 x height and (crown width)2 x crown length separately for each location and the trees above the regression line having highest score for the qualitative characters were selected. This was to ensure that a minimum of one tree got selected from a locality to ensure diversity in selection. The study showed that variability existed for all the qualitative characters and it was more within the localities when compared to between localities. In total twenty five trees were selected. Clustering done for the twenty five plus showed that Melia dubia genetic resources resolved the trees into seven clusters and it was found that grouping were independent to the geographic locations. Inter and intra cluster divergence were also studied. The evaluation of the seedling progenies from the twenty five plus trees were done in the nursery for five months. Significant differences among the progenies of the selected trees were observed for various morphological and physiological characters studied. The performance of the progenies of two trees from Tholpetty (FCV-MD-03 and FCV-MD-04) were the best in most of the parameters studied. The genetic analysis of the causes of variation for the morphological and physiological traits were studied. The values for the phenotypic coefficient of variations ranged from 12.62 per cent for height to 24.53 per cent for biovolume. ii The result indicated that the values for genotypic coefficient of variation was less than the phenotypic coefficient of variations for all the traits studied, indicating existence of environmental effect on these characters. Heritability estimates in broad sense were observed higher than 50 per cent for the quantitative characters such as height, collar diameter, number of leaves, AGR and biovolume. Heritability was also higher for all the physiological characters studied. The genetic gain was also high indicating possibilities of using selections for further breeding. The correlation studies on the morphological and physiological characters showed that the height was positively correlated with all the morphological and physiological characters studied except leaf temperature. Photosynthetic rate was positively correlated with the height, chlorophyll and relative water content of the leaves. For standardization of clonal progenies, cuttings from the seedlings, semi hardwood cuttings from mature trees and root suckers by damaging the roots were taken to develop a method for mass multiplication of the Melia dubia. Three different auxins IBA, NAA, IAA at different concentrations were administered. The result showed that the best treatment for the cuttings and rootsuckers were IBA at 1000 ppm. For the semihardwood cuttings, miniclonal technology was used and the best treatment observed was IBA at 6000 ppm.